Prevelance of Helicobacter pylori in patients with of without dyspepsia and comparsion of different methods in the diagnosis of helicobacter pylori - Mehmet CİNDORUK and Simten AKALIN and Ümit Bilge DOĞAN and Yasemin KOŞAR and Fatih YAKARYILMAZ and Mustafa ÇAĞATAY and İ. Safa YILDIRIM (Turkish Journal of Gastroenterology, 2019)
-